Digital transformation in musculoskeletal ultrasound: acceptability of blended learning - Weimer, Andreas; Berthold, Rainer; Schamberger, Christian T.; Vieth, Thomas L.; Balser, Gerd; Berthold, Svenja; Stein, Stephan; Müller, Lukas; Merkel, Daniel; Recker, Florian; Schmidmaier, Gerhard; Rink, Maximilian Bernhard; et al. (Diagnostics, 2023)
Background: ultrasound diagnostics have a broad spectrum of applications, including among diseases of the musculoskeletal system. Accordingly, it is important for the users to have a well-founded and up-to-date education in this dynamic examination method. The right balance between online and in-class teaching still needs to be explored in this context. Certifying institutions are currently testing digitally transformed teaching concepts to provide more evidence. Methods: this study compared two musculoskeletal ultrasound blended learning models. Model A was more traditional, with a focus on in-person teaching, while Model B was more digitally oriented with compulsory webinar. Both used e-learning for preparation. Participants completed evaluations using a seven-point Likert scale, later converted to a 0-1 scale. Digital teaching media (e-learning) were used for preparation in both courses. Results: the analysis included n = 41 evaluations for Model A and n = 30 for Model B. Model B received a better overall assessment (median: 0.73 vs. 0.69, p = 0.05). Model B also excelled in “course preparation” (p = 0.02), “webinar quality” (p = 0.04), and “course concept” (p = 0.04). The “gain of competence” (p = 0.82), “learning materials” (p = 0.30), and “tutor quality” (p = 0.28) showed no significant differences. Conclusion: participants favorably assessed blended learning in ultrasound teaching. Certifying institutions should consider accrediting models that combine digital methods (e.g., internet lectures/webinars) and materials (e.g., e-learning) with hands-on ultrasound training. Further research is needed to validate these subjective findings for a stronger evidential basis.